Оптимізація параметрів розпушувача плуга для викопування саджанців плодових культур - Матковський, Олександр Іванович; Матковский, Александр Иванович; Matkovskyi, Oleksandr; Саньков, Сергій Михайлович; Саньков, Сергей Михайлович; Sankov, Serhii; Кольцов, Микола Павлович; Кольцов, Николай Павлович; Koltsov, Mykola (ТДАТУ, 2020)
UK: Наведено результати визначення оптимальних параметрів розпушувача робочого органу викопувального плуга. Робочий орган викопувального плуга складається з таких конструктивних елементів: стояку, викопувальної скоби, розпушувача з розпушниками. З розгляду попередніх досліджень потребують вирішення забезпечення умов праці робітників за показниками важкості трудового процесу на вибірки саджанців та підвищення якості посадкового матеріалу. Отримано рівняння регресії для визначення впливу кута нахилу розпушувача до горизонту, довжини важеля, відстані між розпушниками наь зусилля витягування робітниками саджанців. Встановлено, що на зусилля витягування саджанців робітниками з ґрунту досягає 49 Н при таких параметрах розпушувача: кута нахилу поверхні розпушувача до горизонту αр = 320 ; довжини важеля l = 0,42 м; відстані між розпушниками в горизонтальній площини b1 = 0,1 м. За обчисленням середнього значення отримана довжина кореневої системи саджанців перевищувала нормативні технічні вимоги (25 см) на 8,2 см. RU: Приведены результаты определения оптимальных параметров разрыхлителя рабочего органа викопувальних плуга. Рабочий орган викопувальних плуга состоит из следующих конструктивных элементов: стойки, викопочной скобы, разрыхлителя с прутками. Из анализа предыдущих исследований требуют решения обеспечения условий труда рабочих по показателям тяжести трудового процесса на выборки саженцев и повышения качества посадочного материала. Получены уравнение регрессии для определения влияния угла наклона разрыхлителя к горизонту, длины рычага, расстояния между розпушникамы на усилия вытягивания рабочими саженцев. Установлено, что усилия на вытягивания саженцев рабочими из почвы достигает 49 Н при таких параметрах разрыхлителя: угол наклона поверхности разрыхлителя к горизонту αр = 320; длина рычага l = 0,42 м; расстояние между розпушникамы в горизонтальной плоскости b1 = 0,1 м. Среднее значения длины корневой системы саженца превышала норму технических требований (25 см) на 8,2 см. EN: The results of determining the optimal parameters of the baking powder of the working body of a digging plow are presented. The working body of the digging plow consists of the following structural elements: riser, digging staples, baking powder from ripper. The composition of the elements of the actuators that provide the workflow includes: lever, shoe, traverse, control rod, eccentric mechanism. Previous studies examined the improvement of mechanization tools for digging seedlings of fruit crops by creating resource-saving technologies for growing seedlings The influence on the efforts of pulling seedlings from the soil of such parameters of the baking powder: the angle of inclination of the baking powder to the horizon, the length of the lever, the distance between ripper. As a criterion for optimizing the parameters of the baking powder, efforts were made to draw seedlings by workers from the loosened soil during their sampling while ensuring the quality of the seedlings according to technical requirements. Mathematical planning of a full factorial experiment was carried out to determine the influence of the tilting angle of the baking powder to the horizon, the length of the lever, the distance between the ripper on the pulling efforts of the seedlings by workers. The regression equations are obtained to determine the effort for the workers to pull out seedlings from the loosened soil. It is established that the most significant factors are the angle of inclination to the horizon of the surface of the baking powder, the length of the lever and the distance between ripper in the horizontal plane. efforts to pull seedlings by workers from the soil reaches 49 N with the following baking powder parameters: the angle of inclination of the baking powder surface to the horizon αр = 320; lever length l = 0,42 m; the distance between ripper in the horizontal plane is b1 = 0.1 m. According to the calculation of the average value, the obtained length of the root system of the seedling exceeded the norm of technical requirements (25 sm) by 8,2 sm.
Оптимизации параметров рабочего органа плуга для выкапывания саженцев плодовых культур
Optimization of parameters of the working body of the plow for digging seedlings of fruit crops
Keywords: плодовий саджанець; викопувальний плуг; розпушувач; рівняння регресії; зусилля витягування саджанців; параметр; якість саджанців; плодовый сажанець; викопочный плуг; рыхлитель; уравнение регрессии; усилия вытягивания; параметр; качество саженцев; seedlings, digging plow; ripper; regression equation; pulling force parameters; quality seedlings